THE CREDIT EXPERIENCE OF RURAL POPULATION IN ARMENIA - Artak T. Yarazyan (Статистика и экономика, 2016)
This article examines the ﬁ nancial and crediting situation of households employed in the agricultural sector of theRepublic of Armenia. The article examinesthe funding conditions of farms from commercial banks and credit organizations.The agricultural sector is seen before andafter the global ﬁnancial crisis of 2009, and also studies the degree of inﬂuence of ﬁnancial institutions on the living conditions of rural population. This article uses the statistical data of last 10 years toprovide a complete picture and trends ofthe agricultural sector development andthe current funding.